2019
DOI: 10.1590/1806-9061-2018-0758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Enzymatic Blend and Yeast on the Performance, Carcass Yield and Histomorphometry of the Small Intestine in Broilers from 21 to 42 Days of Age

Abstract: The present study was conducted to evaluate the performance, carcass yield, and histomorphometry of the small intestine of broilers fed yeast sugarcane supplemented with enzymatic blend from 22 to 42 days of age. Seven hundred broiler chicks were distributed in a completely randomized design in a factorial design (2x3+1), two levels of the enzyme blend (0 and 200 g/ton), three protein levels (0%, 6% and 12%) and a control diet. The level of 6% yeast showed higher feed intake and weight gain after 33 days. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Live yeast is a rich source of small peptides with free amino acid which has a high rate of digestion and absorption that could effectively improve feed utilization in broilers. A recent study (Sousa et al 2019) reported that when broilers are fed with 6% yeast resulted higher body weight gain with lower FCR during the finisher period, but no differences were observed on feed intake in broilers. Similarly, inclusion of yeast-derived products in broilers diets could improve body weight gain and FCR (Ding et al 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Live yeast is a rich source of small peptides with free amino acid which has a high rate of digestion and absorption that could effectively improve feed utilization in broilers. A recent study (Sousa et al 2019) reported that when broilers are fed with 6% yeast resulted higher body weight gain with lower FCR during the finisher period, but no differences were observed on feed intake in broilers. Similarly, inclusion of yeast-derived products in broilers diets could improve body weight gain and FCR (Ding et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Live yeast (LY) is one of the most potential micro-organism-derived products that can be used in animal ration as a dietary supplement (Sousa et al 2019) as well as a potential alternative to feed antibiotics in animals (Shen et al 2009). Mannanoligosaccharide, derived from the outer cell wall of yeast (Saccharomyces cerevisiae), can be applied as a growth promoter as well as a possible alternative to antibiotics in broiler diets (Yang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although He et al 28 . reported that dietary LY supplementation had no significant effects on ADG and FCR during the whole experimental period, Sousa et al 29 . found that the ADG and FCR during the finisher period were increased in broilers fed diets containing 6% yeast.…”
Section: Discussionmentioning
confidence: 98%
“…A number of researches in poultry have been conducted to evaluate the function of LY, which indicated that LY is an effective feed additive which can improve growth performance and health of broilers. 15,16 Although He et al 28 reported that dietary LY supplementation had no significant effects on ADG and FCR during the whole experimental period, Sousa et al 29 found that the ADG and FCR during the finisher period were increased in broilers fed diets containing 6% yeast. In the present study, we found that dietary LY supplementation (1000 mg kg −1 ) in broilers beneficially increased final BW and ADG, which indicates the improved growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures a rapid rate of digestion and absorption, which could significantly enhance feed utilization. According to a recent study by Sousa et al (35), feeding broilers yeast resulted in increased body weight gain and a decreased feed conversion ratio during the finisher phase, but no alterations in feed consumption were identified in broilers. In the same study, yeast improved protein digestibility in broilers.…”
Section: The Applications Of Baker's Yeast For Broiler Poultrymentioning
confidence: 99%